Differences in the Microrheology of Human Embryonic Stem Cells and Human Induced Pluripotent Stem Cells - Daniels, Brian R. (The Biophysical Society, 2010)
Embryonic and adult fibroblasts can be returned to pluripotency by the expression of reprogramming genes. Multiple lines of evidence suggest that these human induced pluripotent stem (hiPS) cells and human embryonic stem (hES) cells are behaviorally, karyotypically, and morphologically similar. Here we sought to determine whether the physical properties of hiPS cells, including their micromechanical properties, are different from those of hES cells. To this end, we use the method of particle tracking microrheology to compare the viscoelastic properties of the cytoplasm of hES cells, hiPS cells, and the terminally differentiated parental human fibroblasts from which our hiPS cells are derived. Our results indicate that although the cytoplasm of parental fibroblasts is both viscous and elastic, the cytoplasm of hiPS cells does not exhibit any measurable elasticity and is purely viscous over a wide range of timescales. The viscous phenotype of hiPS cells is recapitulated in parental cells with disassembled actin filament network. The cytoplasm of hES cells is predominantly viscous but contains subcellular regions that are also elastic. This study supports the hypothesis that intracellular elasticity correlates with the degree of cellular differentiation and reveals significant differences in the mechanical properties of hiPS cells and hES cells. Because mechanical stimuli have been shown to mediate the precise fate of differentiating stem cells, our results support the concept that stem cell “softness” is a key feature of force-mediated differentiation of stem cells and suggest there may be subtle functional differences between force-mediated differentiation of hiPS cells and hES cells.